Multi-environment analysis to unravel bread wheat core collection to identify donors for grain quality, phenology, and yield traits - Kumari, Jyoti; Gupta, R. K.; Gupta, Arun; Honrao, B. K.; Vaish, S. S.; Sharma, Achla; Ram, Sewa; Krishnappa, Gopalareddy; Sharma, Shivani; Bhardwaj, Rakesh; Jacob, Sherry Rachel; Kumar, Sundeep; et al. (Commonwealth Scientific and Industrial Research Organisation, 2024)
Context Untapped wheat germplasm is conserved globally in genebanks. Evaluating it for grain quality and yield will help achieve nutritional and food security. Aims We aimed to evaluate the Indian National Genebank bread wheat core collection for grain quality, phenology and yield, to identify potential donor germplasm. Methods 1485 accessions were grown at three locations in India during winter 2015–2016 to evaluate test weight, grain protein content, sedimentation value (SV), days to spike emergence, days to maturity, grain yield and thousand-grain weight (TGW). Key results Best linear unbiased estimates indicated mean protein of 13.3%, 14.7%, and 13.0% and yield of 73.0 g/m, 70.9 g/m and 66.6 g/m at Ludhiana, Pune, and Varanasi locations, respectively. The SV ranged from 26.6–65.6 mL and 17.7–66.6 mL at the Ludhiana and Pune locations, respectively. The top 10 accessions were identified for all the studied traits. Six high protein accessions, with consistent protein of more than 15% along with moderate Thousand-grain and test weights were further validated and assessed for stability across environments. Grain protein content was correlated negatively with thousand-grain weight and yield, but positively with days to maturity and spike emergence. Conclusion The identified accessions with high trait values could be used in future breeding programmes to develop high yielding biofortified cultivars to address protein malnutrition and also cultivars with suitable end-product quality. Implications The diversity in a core collection can be exploited to develop modern high yielding bread wheat cultivars with higher grain protein content and suitable end-product quality.